Thermal and mechanical properties of in-house-manufactured PLA and PA filaments at high temperature - Mohd Radzuan, Nabilah Afiqah; Mat Samudin, Izzat; Al-Furjan, M. S.H.; Sulong, Abu Bakar; Mohd Foudzi, Farhana; Azman, Muhammad Amin (Institute of Metals Technology, 2025)
Fused-filament fabrication using thermoplastic polymers such as polylactic acid (PLA) and polyamide (PA) is widely employed to fabricate high-quality products. However, at high temperature, filaments exhibit reduced mechanical performance because of their low thermal stability. This study aims to fabricate in-house PLA and PA filaments and evaluate their mechanical properties and printability in comparision with those of conventional filaments. Compression tests reveal that at 120°C, in-house PA achieves a high strength of 125.8 MPa, outperforming conventional PA and PLA with strengths of 50 and 102 MPa, respectively. The performance of in-house PA is better than that of in-house PLA because of the different polymer structure and chemical composition of PA. Flexural tests show that in-house PLA has a high Young’s modulus of 2,675 MPa, which is 18 times higher than that of in-house PA at 144.5 MPa. Experimental data reveal improved performance when compared with finite-element analysis, with an increment of 23 times for in-house PLA and 63% for in-house PA. These findings indicate that in-house-fabricated PA filaments are on par with conventional PA filaments, especially when tested at a maximum temperature of 60°C. In-house-fabricated PLA and PA filaments demonstrate superior mechanical performance and thermal resilience, making them competitive alternatives to conventional filaments for high-temperature applications.